(untitled) (Cultura Económica, 2019)
This article deals with the interpretation of the Argentine economic growth through the development of a local capital market. Both the historical experience as well as the academic debate reflect the close relationship between economic growth and the development of local financial markets. In fact, the underdevelopment of financial markets in Argentina is one of the most serious vulnerabilities that limits the possibilities of achieving a sustained process of growth with social inclusion. The aim of this article is to present an analytical review of the Argentine experience, which suggests the existence of institutional and cultural constraints that hinder the development of a local capital market. The article shows the implications that this has for the real economy and tests possible explanations and answers in the light of the analysis of institutional economics.